Family Planning Counseling Capacity in Improving Family Knowledge During the Covid-19 Pandemic - Putri Santy (Science Midwifery, 2022)
Practical steps are needed to overcome various demographic challenges, and one of the programs considered important is Family Planning (KB). Through family planning, standardize birth, ideal birth interval and reproductive age, control pregnancy period, and promote, guarantee and support reproductive rights to build high-quality families. Family planning programmes enable women to manage their pregnancies and reduce maternal mortality. Given the importance of counseling in the success of family planning programs, this review study aimed to further explore the ability of family planning counseling to increase family knowledge during the COVID-19 pandemic. This study is a systematic review using online databases namely Scholar, ScienceDirect, and ProQuest. The keywords used were Family Planning, Family Knowledge, Pandemic, Covid-19 . The selection process used the PRISMA protocol, resulting in 15 articles that met the inclusion criteria. The results of the study show that most family planning cadres had high skill levels during the epidemic, but the overall level of family knowledge was still low. This is due to obstacles such as community cultural development, a limited number of family planning teachers, limited family planning service facilities and infrastructure, and lack of public awareness of family planning work. But overall, family planning programs are supported by the community and religious leaders, capable field workers, and scientific and technological developments. Families' knowledge of family planning relies on consultants, especially medical staff and family planning consultants, as sources of information. Mass media resources are very limited.